Assessing the applicability of sentinel-2 remote sensing data to determine the bathymetry of a shallow coastal area: case study of Nhat Le Estuary, Quang Binh Province - Le, Duc Hanh; Hoang, Thanh Son; Tong, Phuc Tuan; Vu , Hai Dang; Nguyen, Ngoc Thang; Bui, Anh Tuan; Tran, Thai Binh; Trinh, Viet Nga; Tran, Anh Tuan (Vietnam Journal of Marine Science and Technology, 2025)
Seabed mapping is complex and expensive because it is often performed in a harsh environment sensitive to weather factors. To overcome these limitations, there have been many studies on the application of remote sensing data to measure the seabed depth based on physical laws about the attenuation of reflected energy of light when passing through a water column. The value of reflected energy from the seabed on remote sensing images is used to determine the depth of the seabed. Worldwide, studies have been conducted on applying remote sensing data to measure seabed depth through the modeling and GEE cloud computing platforms. There are also studies in Vietnam that map the seabed topography for offshore islands. This paper measured the seabed depth based on experimental data, survey lines conducted in April and October 2018, and Sentinel 2 remote sensing images data for Nhat Le estuary area. The paper aims to review and evaluate the correlation and accuracy of the application of Sentinel-2 remote sensing image data to measure the depth of the seabed topography for shallow coastal waters. The results show that the correlation coefficient R2 along the surveyed lines is from 0.84 to 0.94, and the mean RMSE ranges from 0.70 to 0.74. The above assessment shows that surveyed lines that can be employed to interpret a larger area in the same satellite image scene using the empirical formula in the study area. The formula can also be used to determine the depth of bottom topography for other geographical areas with similarities in seawater turbidity and bottom material, as well as technical issues.